Indonesian Beck Depression Inventory Adaptation and Validation Among Nursing Students: A Cross-Sectional Study - Dian Sari; Dian Fitria; Irna Kartina; Retno Lestari; Andi Buanasari; Indah Putri Ramadhanti; Siti Mutia Kosassy (Persatuan Perawat Nasional Indonesia (JPPNI), 2026)
BackgroundThe Beck Depression Inventory (BDI) is widely used to assess depressive symptoms; however, its validity among Indonesian nursing students has not been established.ObjectiveThe objective of this study to translate the BDI into Bahasa Indonesia and evaluate its psychometric properties among Indonesian nursing students.MethodsThe study followed the framework of adaptation and validation of instrument scale by Sousa and Rojjanasrirat. A total of 709 nursing students in Indonesia were participated with eligible criteria: actively enrolled; no history of mental health disorder and not currently on routine medication prescribed by a psychiatrist. Validity testing included exploratory and confirmatory factor analyses (EFA and CFA), concurrent validity, and assessment of ceiling and floor effects. Reliability was assessed using Cronbach’s alpha.ResultsEighteen items were retained. Internal consistency was high (Cronbach’s alpha = 0.914). EFA supported a three-factor structure: Negative Attitude, Somatic Symptoms, and Impaired Performance with factor loadings 0.376 to 0.684 (KMO= 0.946; Bartlett’s test p < 0.001). CFA demonstrated acceptable model fit. Ceiling and floor effects were minimum (7.7% amd 0.01%, respectively). Concurrent validity showed a strong correlation with the DASS-21 with depression subscale (r = 0.72, p < 0.001).ConclusionThe 18-item Indonesian BDI is a valid and reliable instrument for assessing depression severity among Indonesian nursing students and can be recommended for assessing depression among nursing students.KeywordsDepression, mental health, nursing student, reliability, validity